Kepercayaan mahasiswa terhadap kompetensi dan kedekatan dalam interaksi antara mahasiswa dan dosen - Faradillah Firdaus; Asmulyani Asri (Seminar Nasional LP2M UNM, 2019)
This study aims to look at student confidence in competence and closeness in the interaction between students and lecturers. This research was conducted at the Faculty of Psychology, Makassar State University involving 150 students. The subject of this study was measured through the trustworthiness scale. This study uses simple regression analysis to see the influence of competencies possessed by lecturers on student trust. From the results of regression calculations, the coefficient of -0.394 is obtained, besides it has a t-count of -3.576 <t table 1.654 and has significance amounting to 0.00 <0.05, so the lecturer competency hypothesis has a negative effect on student confidence in lecturers, accepted. Whereas the influence of the lecturers' attachment to the student's trust. From the results of the regression calculation, the coefficient obtained is 0.561, besides that it has a t value of 6.844 greater than t table 1.654 and has a significance value of 0.00 <0.05, so the hypothesis "lecturer and student attachment has a positive effect on student confidence in lecturers" can be accepted.